Studies on ferromagnetic shape memory Ni-Mn-Ga alloys with Fe and rare-earths additives - Singh R.K.; Raja M.M.; Mathur R.P.; Shamsuddin M. (My University, 2025)
The effect of Fe and rare-earths (Tb&Dy) addition on the martensitic transformation, magnetic and mechanical properties of the Ni50Mn 30Ga20 (at%) ferromagnetic shape memory alloy was investigated. The results show that the rare-earths exhibit negligible solubility in the Ni-Mn-Ga-Fe matrix phase and formed grain boundary phase. The grain boundary precipitate enhances the compressive ductility of the alloys. The martensite transformation temperature was found to be increased by the addition of rare-earths, while, Fe increased the Curie temperature of the Ni-Mn-Ga alloy. However, with increase in Fe content, an additional (Ni,Fe) 3(MnGa) precipitate is formed, leading to decrease in martensite transformation temperature and compressive ductility. © 2010 Elsevier B.V. All rights reserved.